A Dynamic Cycle of Familial Mental Illness. (1st December 2014) - Murphy, Gillian; Peters, Kathleen; Wilkes, Lesley; Jackson, Debra
<x xml:space="preserve">Abstract</x> In this paper, we present A Dynamic Cycle of Familial Mental Illness; an innovative framework, which considers family members' experiences and responses to mental illness. There is an acknowledged discourse noting parental experiences of mental illness alongside a growing body of knowledge acknowledging children's needs while living with parental mental illness. However, there is a paucity of literature that makes reference to the concept of familial mental illness and the cyclic interface of parental and child distress and symptoms. The model is supported by published research studies from several differing disciplines to demonstrate the relationship between parent and child experiences and to synthesise the published short- and longer-term possible impact of familial mental illness. An extensive search of the literature using recognised search engines, keywords and phrases has been undertaken, to generate an appropriate literature base for this work. This literature demonstrates how a child's possible emotional distancing as a response to parental mental illness could increase parental distress. A Dynamic Cycle of Familial Mental Illness adopts the underpinning philosophy of a Stress Vulnerability Model of Mental Illness, which assumes that predisposing factors and increased stress for a parent may have possible links to exacerbation of parental mental distress and symptomology. We advocate for further research of familial mental illness, and argue for a family approach to mental health assessment and treatment in mainstream health and social care sectors.